Changes in agricultural scenario of Madhya Pradesh with special reference to soybean in changed climatic scenario: A study on farmers’ perception: CHANGES IN AGRICULTURAL OF MADHYA PRADESH WITH SPECIAL REFERENCE TO SOYBEAN - PURUSHOTTAM SHARMA; B U DUPARE; S D BILLORE; S K VERMA (Journal of Oilseeds Research, 2020)
This study examined soybean growers’ perception about climate change and variability, and their adaptation strategies in response to the perceived impacts of climate change. The multi-stage sampling method was employed to select 280 rural farmers in Dewas, Indore and Dhar districts located in Malwa plateau and Nimar valley ofMadhya Pradesh. The results revealed that the crop diversification is lost over a period of time and monocropping ofsoybean became popular in the study area. The introduction ofsoybean was found to be instrumental for enhancement in the cropping intensity ofthe area. Among abiotic weather-related stresses perceived bymajority offarmers were delayed arrival of monsoon, uneven and erratic rainfall, reduced number of rainy days, increased temperature and sunshine hours, and the reduced humidity. Majority of farmers perceived a decrease in annual rainfall. They also perceived that the biotic stresses (weeds, insects and diseases) had increased significantly over a period of time. All these factors were responsible for low yields. Survey also indicated that the mechanization increased substantially, and short duration varieties replaced the long duration soybean varieties. To reduce the perceived impacts of climate change, farmers adopted various farm-level adaptation strategies. The results of this study will provide baseline information for local governments, researchers, and policy-makers on farmers’ perception of climate change and adaptation strategies.